The concept of creating an information technology of process formation of the main educational programs based on professional competencies (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper gives the definition of information technology, describes the concept of creating an Information Technology of process formation of Main Educational Programs (IT MEP) based on professional competences and gives conceptual scheme of creating IT MEP.